Chronodisruption that dampens output of the central clock abolishes rhythms in metabolome profiles and elevates acylcarnitine levels in the liver of female rats - Arora, Shiyana; Houdek, Pavel; Čajka, Tomáš; Dočkal, Tereza; Sládek, Martin; Sumová, Alena (Acta physiologica (Oxford, England), 2025)
AIM: Exposure to light at night and meal time misaligned with the light/dark (LD) cycle-typical features of daily life in modern 24/7 society-are associated with negative effects on health. To understand the mechanism, we developed a novel protocol of complex chronodisruption (CD) in which we exposed female rats to four weekly cycles consisting of 5-day intervals of constant light and 2-day intervals of food access restricted to the light phase of the 12:12 LD cycle. METHODS: We examined the effects of CD on behavior, estrous cycle, sleep patterns, glucose homeostasis and profiles of clock- and metabolism-related gene expression (using RT qPCR) and liver metabolome and lipidome (using untargeted metabolomic and lipidomic profiling). RESULTS: CD attenuated the rhythmic output of the central clock in the suprachiasmatic nucleus via Prok2 signaling, thereby disrupting locomotor activity, the estrous cycle, sleep patterns, and mutual phase relationship between the central and peripheral clocks. In the periphery, CD abolished Per1,2 expression rhythms in peripheral tissues (liver, pancreas, colon) and worsened glucose homeostasis. In the liver, it impaired the expression of NAD+, lipid, and cholesterol metabolism genes and abolished most of the high-amplitude rhythms of lipids and polar metabolites. Interestingly, CD abolished the circadian rhythm of Cpt1a expression and increased the levels of long-chain acylcarnitines (ACar 18:2, ACar 16:0), indicating enhanced fatty acid oxidation in mitochondria. CONCLUSION: Our data show the widespread effects of CD on metabolism and point to ACars as biomarkers for CD due to misaligned sleep and feeding patterns.
Keywords: Circadian Rhythm; cirkadiánní rytmus; Carnitine; suprachiasmatic nucleus; Female; krysa rodu Rattus; metabolom; cirkadiánní hodiny; metabolome; liver; karnitin; potkani Sprague-Dawley; acylcarnitine; chronodisruption; Metabolome; Circadian Clocks; pancreas; Photoperiod; Rats, Sprague-Dawley; zvířata; rat; játra; clock; ženské pohlaví; fotoperioda; Liver; glucose homeostasis; Rats; Animals; female; sleep